(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
The aim of this research is to determine a simulation of an electric control unit (ECU) for direct injection compression ignition combustion engine, in order to improve an engine performance and reduced fuel consumption. The simulation comprises thermodynamic model for determining engine parameters according to Spray Penetration Mixing Length, and imposes in Matlab and Simulink. This model allows closed loop control interferences with Arduino MEGA-2560 to manage amount of injected fuel and start of injection that, could be lead to obtain the optimum thermodynamic energy. The results of thermodynamic model show that, the engine parameters can be related linearly, and matching the other published researches on the same conditions and specifications. The results of (ECU) show synchronization between desired and output signals and appear more accuracy when compared with other methods.